2018
DOI: 10.1186/s12950-018-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

The severity of LPS induced inflammatory injury is negatively associated with the functional liver mass after LPS injection in rat model

Abstract: BackgroundHigh levels of serum lipopolysaccharide (LPS) were observed in sepsis patients with liver injury and high mortality. However, the role of liver in modulation LPS induced inflammatory injury was ill investigated. In the present study, the severity of LPS induced inflammatory response was observed after liver resection or portal branch occlusion to decreasing functional liver mass. The local and systemic damage was observed to investigate the role of liver in modulation inflammatory injury.MethodsFirst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
3
21
0
2
Order By: Relevance
“…The toxic issues of LPS are mediated by cytokines like TNF-α, interleukin 1 (IL-1), and IL-6 released by LPS-activated host cells, such as neutrophils and macrophages. Several studies have shown that initial pro-inflammatory cytokines increase rapidly within 30 min after LPS injection [31,32]. Our recent cellular biodistribution findings also confirm the significant therapeutic effect of exosome carrying srIKB during the early stage of sepsis before the immunosuppressive state [30].…”
Section: Resultssupporting
confidence: 83%
“…The toxic issues of LPS are mediated by cytokines like TNF-α, interleukin 1 (IL-1), and IL-6 released by LPS-activated host cells, such as neutrophils and macrophages. Several studies have shown that initial pro-inflammatory cytokines increase rapidly within 30 min after LPS injection [31,32]. Our recent cellular biodistribution findings also confirm the significant therapeutic effect of exosome carrying srIKB during the early stage of sepsis before the immunosuppressive state [30].…”
Section: Resultssupporting
confidence: 83%
“…However, the correlation of lncRNA CASC7 with miR-217 and TLR4 in the modulation of sepsis-induced liver injury is still elusive. Lipopolysaccharide (LPS) serves as the endotoxin that is issued by bacterial membranes and interacts with receptors on the surface of endothelial cells, whereby working as a noxious factor that produces acute in ammation [25]. LPS has been identi ed to cause sepsis by modulating the oxidative stress or in ammatory factors, and the growth of endothelial cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the inflammatory response helps the organism to clear the LPS or pathogen. However, the violent inflammation caused by overproduced LPS could lead to tissue damage [ 28 ]. In the present study, the inhibitory effect of isolates 1 – 8 against the enhanced production of inflammatory factors in LPS-treated murine macrophage J774A.1 cells was examined.…”
Section: Introductionmentioning
confidence: 99%